See Answer

### Answer with Explanation

Answer is 9.

**How?**

Here, every middle element is the sum of the other two so answer should be 6+3 = 9.

See AnswerHide Answer

Answer is 9.

**How?**

Here, every middle element is the sum of the other two so answer should be 6+3 = 9.

by Ankur 4 Comments

See AnswerHide Answer

Answer is 54325

How?

Just keep appending the new number to the previous answer 🙂

by Ankur 2 Comments

See AnswerHide Answer

Given

6 – 1 x 0 + 2 / 2

= 6 – 0 + 1

= 7

See AnswerHide Answer

Given

11×11 = (1+1)*(1+1) = 4

12×12 = (1+2)*(1+2) = 9

13×13 = (1+3)*(1+3) = 16

See AnswerHide Answer

Given 1 = 1^1 + 1,

4 = 4*4 + 4 = 20

6 = 6*6 + 6 = 42

9 = 9*9 + 9 = 90

10 = 10*10 + 10 = 110

See AnswerHide Answer

Given 1 = 5,

2 = 5*2 + (1) = 11

3 = 11*3 + (1 + 2) = 36

4 = 36*4 + (1 + 2 + 3) = 150

5 = 150*5 + (1 + 2 + 3 + 4) = 760

- « Previous Page
- 1
- …
- 20
- 21
- 22